Sustained signaling through the B-cell receptor induces Mcl-1 and promotes survival of chronic lymphocytic leukemia B cells - Petlickovski, Aleksandar; Laurenti, Luca; Li, Xiaoping; Marietti, Sara; Chiusolo, Patrizia; Sica, Simona; Leone, Giuseppe; Efremov, Dimitar G (American Society of Hematology, 2005)
The clinical course of chronic lymphocytic leukemia (CLL) differs significantly between patients with mutated (M-CLL) and unmutated (U-CLL) immunoglobulin (Ig) variable heavy-chain (V(H)) genes, implying a role for B-cell receptor (BCR) signaling in the pathogenesis of this disease. We have now investigated activation of downstream BCR signaling pathways in U-CLL and M-CLL B cells using soluble anti-IgM (sol-IgM) and immobilized anti-IgM (imm-IgM) antibodies as models for antigenic stimulation. Ligation of the BCR with sol-IgM induced incomplete responses in both CLL subsets, resembling the pattern described for tolerant B cells. This response was characterized by transient phosphorylation of extracellular signal-related kinase (ERK) and Akt (protein kinase B [PKB]), lack of activation of c-JUN NH2-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK), and variable activation of phospholipase Cgamma2 (PLCgamma2) and nuclear factor-kappaB (NF-kappaB). Stimulation with imm-IgM elicited a more complete BCR signal and significantly prolonged phosphorylation of ERK and Akt, indicating persistent or repetitive BCR signaling. Moreover, this type of stimulation increased the levels of the antiapoptotic protein myeloid cell leukemia-1 (Mcl-1) and protected from chemotherapy-induced apoptosis, whereas induction of apoptosis and down-regulation of Mcl-1 was observed following stimulation with sol-IgM. These data demonstrate that only sustained BCR signaling can promote survival of CLL B cells and indicate that the main difference between CLL with mutated and unmutated V(H) genes may reside in the availability of such stimulation.